How cooperative learning strategies enhance communicative skills in a fourth grade efl class at Nahim Isaías Barquet school - Prieto Gómez, Ana Elizabeth (2016)
The purpose of this thesis is to investigate and analyze the effects of using Cooperative Learning strategies to enhance Communicative Skills in a fourth grade EFL class at Nahim Isaias Barquet School in Ecuador. Over the last fifty years Cooperative Learning techniques have improved the teaching learning process increasing student´s motivation and team work. For that reason, to evaluate in a deep way each research instrument, it was necessary to apply a mixed research type “quantitative and qualitative” in which the application of the deductive and the inductive method, as well as, the analysis and the synthesis of the literature review were important to inquire, to value and to selfassess the investigation. On the other hand, the population was based on fourteen students which had communicative problems in the use of a foreign language. The techniques that the researcher applied were: semi-structured interviews to English teachers, teacher´s grade book and surveys. The analysis was based on the academic performance and in the teacher´s development and classroom management those analyzes are going to answer the following query Which is the impact of the application of Cooperative Learning strategies on fourth graders at Nahim Isaias Barquet School? The results were shown in bar charts and graphics which guide the researcher to identify the impact of the project in the education community. The application of Cooperative Learning strategies in this study helps teachers in their teaching process to enhance pupils to listen to each other´s opinions by asking questions, clarifying issues and re-stating points of view….